Response to strategic dietary mineral mixture supplementation in cattle and buffaloes under field condition (Hill region) of Nainital district of Uttarakhand - TIWARI, S K; KUMAR, ANIL; TIWARI, D P; MONDAL, B C; SAXENA, P C (The Indian Journal of Animal Sciences, 2012)
Calcium, phosphorus, zinc, manganese and copper were found below the critical level in soil, feeds and blood serum of cattle and buffaloes in hill region of Nainital district of Uttarakhand. A study was, therefore conducted to see the effect of dietary supplementation of these minerals as area specific mineral mixture in cattle and buffaloes on reproductive performance, milk yield, their profile in blood serum under field condition in four villages of Nainital district. The calcium, phosphorus, zinc, manganese and copper were supplemented in the form of feed (mineral) mixture which contained ground maize 32.80%, mustard cake 48.69%, di-calcium phosphate 17.85%, copper sulphate 0.12%, manganese sulphate 0.30% and zinc sulphate 0.24%. Fifteen animals (cattle and buffaloes) of different physiological status from each village were selected. Each selected animal was provided 250 g feed mixture daily in order to supply 12 g calcium, 5 g phosphorus, 250 mg zinc, 175 mg manganese and 60 mg copper over and above already present in the ration of animals provided by the farmers for 45 days. The incidence of the anoestrus and repeat breeding cases decreased due to dietary supplementation of area specific mineral mixture. Milk yield was increased and remained persistent in lactating (pregnant) and lactating (non-pregnant) animals. The SGPT, SGOT and ALP activities increased in all categories of animals but were within the normal range. Blood serum calcium and phosphorus concentrations were also increased significantly and reached above their critical levels (8.00 mg/dl and 4.00 mg/dl respectively) in all categories of animals. The serum zinc, manganese and copper concentration also increased but not significantly due to dietary supplementation of these minerals. It was concluded that area specific mineral mixture supplementation in the ration is inevitable in amelioration of reproductive problems and in improving the milk production, reproductive performance and mineral profile in cattle and buffaloes under field condition of Kumaun hill region.